ANALISIS KOMITMEN ORGANISASI DALAM PENINGKATAN TARGET ON TIME PERFORMANCE (OTP) - Muhammad Imam Muttaqijn; Muhammad Imam Muttaqijn (Universitas Muhammadiyah Tangerang, 2020)
This study aims to analyze organizational commitment in increasing the target On Time Performance (OTP) of PT. Citilink Indonesia. The research approach used in this study is a qualitative approach using qualitative descriptive. Data collection techniques used by researchers are observation, interviews and documentation. The data source in this study is divided into two, namely primary data and secondary data. Data collection techniques used by researchers in this study is the data triangulation method. Analysis of the data used through three stages, namely data collection, data classification and conclusion drawing The results of this study indicate that; 1) airline organization commitment of PT. Citilink Indonesia can be said to be quite good because it saw an increase in the On Time Performance (OTP) target from 2018 only 85% and 2019 becomes 90%. In 2019 On Time Performance (OTP) was achieved with a figure of 92% 2). The analysis shows that organizational commitment is an important factor in increasing the target of On Time Performance (OTP) of PT. Citilink Indonesia. Because with the organizational commitment of employee performance in achieving the target On Time Performance (OTP) at PT. Citilink Indonesia can be achieved in 2019 has increased